11x+8-4x=-9x-10+x

Simple and best practice solution for 11x+8-4x=-9x-10+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11x+8-4x=-9x-10+x equation:


Simplifying
11x + 8 + -4x = -9x + -10 + x

Reorder the terms:
8 + 11x + -4x = -9x + -10 + x

Combine like terms: 11x + -4x = 7x
8 + 7x = -9x + -10 + x

Reorder the terms:
8 + 7x = -10 + -9x + x

Combine like terms: -9x + x = -8x
8 + 7x = -10 + -8x

Solving
8 + 7x = -10 + -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
8 + 7x + 8x = -10 + -8x + 8x

Combine like terms: 7x + 8x = 15x
8 + 15x = -10 + -8x + 8x

Combine like terms: -8x + 8x = 0
8 + 15x = -10 + 0
8 + 15x = -10

Add '-8' to each side of the equation.
8 + -8 + 15x = -10 + -8

Combine like terms: 8 + -8 = 0
0 + 15x = -10 + -8
15x = -10 + -8

Combine like terms: -10 + -8 = -18
15x = -18

Divide each side by '15'.
x = -1.2

Simplifying
x = -1.2

See similar equations:

| x^2+20x-15=6 | | 4(d-2)+5= | | 5-3(1-x)=-16 | | 7(4x+8)-6=106 | | f(2.885)=-5.89+6.357 | | 6x^2+7=13 | | 5y+3=2y+20 | | 2ln(x)+ln(6x+7)=ln(9x-2) | | 3(2d-1)-2d= | | b-(-17)=12 | | logy=-12.1886 | | 0.35x+0.05(6-x)=0.10(39) | | -7v^2=-252 | | k^2+40=-13k | | 2(3a-4)=4(5-2a) | | 9(2x-3)-4(5+3x)=5(6+x) | | -4(3+x)+5=4(x+3)+5 | | 3=-2x-7 | | 5-3(1-x)=16 | | 0.20x+0.05(18-x)=0.10(3) | | 5k^2-6=119 | | 5(6c-5)-[3(3c-3)+3]= | | Ln(x^2)+5ln(x)-9ln(x)=-9ln | | 1+2i+3(i*i)= | | 3v^2=108 | | 24x^2+-24x+6=0 | | 0=y^2-2 | | 5log(7x-1)=25 | | 7x+7=6x+4 | | 4x-8=-36+3x | | 7z=-8 | | 60.6=x-16.8 |

Equations solver categories